الثوار الهنود خلال الحرب العالميه الاولى دراسه لاهدافهم ونقاط ضعفهم 1914 - 1918 م - مصطفى، هيثم علوان (جامعة الموصل - كلية التربية الأساسية, 2010)
كان الثوار الهنود خلال فترة البحث على أتم استعداد لتبني أية وسيلة تخدم أغراضهم، وكانت أولى خطواتهم متمثلة بتحريض أبناء الشعب الهندي على تحدي نظام الحكم البريطاني في الهند الذي استمر قرونا عديدة. \ غير أن الضعف الحقيقي للثوار الهنود كان على صعيدي الفكر والتنظيم ولم يكن لدى الكثير منهم أية فكرة واضحة عن طبيعة الاستقلال والعمليات اللازمة لتحقيق. وعلى الرغم من أن الاستخبارات البريطانية كانت فعالة جدا بشكل يفوق مقدرتهم وكانت في أغلب الحالات على علم مسبق بخطط وتحركات الهنود إلا أن جهودهم تلك منحت الحركة الوطنية الهندية دافعا كبيراً واندفاعا عاطفيا لا مثيل له. \ وتضمنت محاور البحث سبعة عناوين رئيسية، وهي: مجموعات ثورية متباينة، وفرصة اندلاع الحرب العالمية الأولى، والمساعدات الخارجية لثوار الهند، وصعوبات داخلية ونقاط ضعف، ونظرة حول المتطلبات الأساسية، والضعف الحقيقي يكمن في الفكر والتنظيم وأخيرا تساؤلات وملاحظات عديدة. The Indian revolutionaries during the resurgence period were quite ready to adopt any means that service their purpose . Their first step was to urge the Indian people to challenge the Raj in India which lasted many centuries . \ However , the actual weakness of Indians revolutionaries was in the levels of ideology and organization , and many of them had no clear idea about the nature of independence and the necessary means to achieve it . Although the British intelligence was too far beyond their power , and in many cases it had a prior knowledge of the Indians plans and movement , their efforts gave the Indian national movement a tremendous motive and unprecedented passionate impulse . \ The axes of the research included the following seven headlines ; Disparate revolutionary groups . Chance of first world war outbreak . The outside aids to the revolutionaries of India . Domestic difficulties and weakness . An outlook at some essential requirements . The actual weakness lies in the organization . Finally , many questions and remarks .
Keywords: الدوله العثمانيه -- الهنود -- الثوره الهنديه -- الحرب العالميه الاولى -- الاحتلال البريطانى للهند -- الاستقلال